The change in the level of concentration of the enzyme troponin and Myoglobin (Mb) after The Microcycle a training with the maximum strength with basketball players - Taha, Ahmed (Journal of Physical Education, 2015)
1. The change in the level of concentration of the enzyme troponin and Myoglobin (Mb) after The Microcycle a training with the maximum strength with basketball players 2. Identification of the Research contain:- The training process has become more closely associated with the means of physiological, psychological, and biological, as this means that the combined contribute to reduce pain and fatigue and muscle and try to reach high degrees of physical and physiological efficiency. Accompanied by a high-intensity physical training the emergence of a muscular pain of the factors that lead to reduced access to advanced stages of physical and physiological efficiency in athletes. The problem of the research contains: Identify the concentration of myoglobin (Mb) and Troponin enzyme troponin in the blood in the tribal measurement (before pregnancy To topics related to the study which is the enzyme troponin and myoglobin and load cycle training Minor and telemetric first (after the end of the training Microcycle a training with the maximum strength(The Microcycle) with the experimental group. Identify the concentration of myoglobin (Mb) and troponin in telemetric after the second (2) hours of dimensional measurement with the first experimental group. The aims of the resaerch: Determine the effect of the unit weekly training weekly Microcycle a training with the maximum strength on the level of concentration of the enzyme troponin and myoglobin. The extent of the change in the level of enzyme troponin and myoglobin after Module weekly the maximum strength(The Microcycle) directly, and after (2) hours of training module. The assumption of the research: There are statistically significant differences between the measurement and tribal telemetric first in the concentration of myoglobin and troponin enzyme in the blood for the benefit of telemetric first. There are statistically significant differences between the first and telemetric telemetric second in the concentration of myoglobin and troponin in the blood for the benefit of telemetric second. 3. Theorical and similar studies: To topics related to the study which is the enzyme troponin and myoglobin (Mb) and load cycle training (The Microcycle). 4. The research procedure itis field performance:- The researcher used the experimental method to solve the problem of the research, and the research community players club Suleikh basketball of the season 2013-2014 the number of members of the sample (5) players have been selected in the manner intentional, and was then an experiment president either statistical methods are (arithmetic mean, standard deviation , the mediator, (v) of the samples correlated). 5. Peresentation Analyzing and Discussion the result:- As to ensure present and discuss the relationship between voltage Alp ne higher intensity in the training module micro weekly maximum intensity and the level of concentration of the enzyme troponin and myoglobin. 6. Conclusions and Recommendations: 6.1 coclusion as follow: 1. that the enzyme troponin increases after physical effort , especially the high intensity type of troponin (I), which is more responsive to the physical effort and even after two hours of effort. 2. No Ertqa enzyme troponin at rest , which was given to the research sample , and this means there is no condition of the heart muscle , when my father brings comfort is the type of troponin (T). 3. Height Almiocalobin compound which serves to provide oxygen to the muscles and heart when myoglobin decrease , because it works on the level of oxygen and sessile. 4. lack of adequate rest periods between interfacial strenuous exercise extreme severity and lack of interest in re- hospitalization through the exercise of jogging and light exercises Altmtih after the end of the module , causing a high level of troponin and myoglobin and continued to rise until two hours after the end the exercise.. 6.2 The researcher recommended by: 1. Attention to measure variables Alksaologih and biochemical pre-season training to get the best results in training and competition. 2. The need for periodic examination of the heart muscle , by measuring the level of the enzyme troponin being affected by the constant effort and a height of causing myocardial infarction. 3. myoglobin measure gives an indication of the index and get the heart muscle and a sufficient amount of oxygen being more attached to oxygen when voltage. 4. The use of various means such as hospitalization Altmtih exercises , jogging and light exercises and pneumatic variety, nutrition , convenience interfaces between exercises , after high-intensity effort. 5. intake of magnesium with calcium, so calcium regulation and by following Tntam muscle action and regulate heartbeat